Significance of phospholipase A2 inhibitor Annexin A1 in type 2 diabetes mellitus with foot ulcers - Shwetha Shetty Kalladka, Rajashekar Mohan, Praveenkumar Shetty, Prakash Patil (Journal of Applied Pharmaceutical Science, 2024)
A chronic, low-grade inflammation is the significant pathogenic feature involved in the development of type 2 diabetes mellitus, which is becoming more prevalent worldwide. Annexin A1 (ANXA1), an endogenous glucocorticoid-regulated protein is known to restore homeostasis by counteracting inflammatory processes. This study aimed to determine the role of circulatory and tissue ANXA1 levels in the pathophysiology of diabetic foot ulcers and also find its correlation with other inflammatory regulators and the clinical-investigative profile of study subjects. The serum and wound tissue from a total of 40 subjects including diabetic subjects with foot ulcers (n = 20) and non-diabetic subjects (n = 20) were analyzed for the levels of ANXA1 and other inflammatory regulators such as IL1β, IL6, IL10, and TNFα by sandwich enzyme-linked immune-sorbent assay. Pearson’s correlation coefficient analysis was performed to find the association between the ANXA1 levels and the clinical-investigative profile of diabetic foot ulcers. The levels of circulatory and tissue anti-inflammatory ANXA1 were lower in diabetics, compared to non-diabetic foot ulcers. However, the pro-inflammatory regulators IL1β, IL6, and TNFα levels in tissue and serum were upregulated in diabetics with foot ulcers. Further, the levels of ANXA1 have having good association with diabetic foot ulcers as well as with other inflammatory regulators and are more significant in serum, compared to the levels in tissue samples. Overall, the lower levels of anti-inflammatory ANXA1 in diabetic foot ulcers indicate their role in the inflammation homeostasis that is essential for the initiation of wound healing.
Keywords: Diabetes mellitus, foot ulcers, inflammation, annexin A1, wound healing